Review of the Afrotropical genus Dwightla McKamey (Hemiptera: Cicadellidae: Deltocephalinae: Selenocephalini) with description of a new species from Nigeria - Lu, Lin; Zhang, Yalin (Zootaxa, 2018)
The Afrotropical leafhopper genus Dwightla previously included five species: D. acutipennis (Linnavuori & Al-Ne’amy), D. alecto (Linnavuori & Al-Ne’amy), D. angolana (Linnavuori & Al-Ne’amy), D. delongi Zahniser & Dietrich and D. hercules (Linnavuori & Al-Ne’amy). A new species, Dwightla medleri sp. nov. from Nigeria, is described and illustrated and a checklist and key to species of this genus are provided.